2016
DOI: 10.1021/acs.langmuir.6b00282
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transfer and Surface Functionalization of Hydrophobic Nanoparticle using Amphiphilic Poly(amino acid)

Abstract: Functionalization of nanoparticles with chemical and biochemical is essential for their biomedical and other application. However, most of the high quality nanoparticles are hydrophobic in nature due to surfactant capping and their conversion into water-soluble functional nanoparticle via appropriate coating and conjugation chemistry is extremely critical issue. Here we report amphiphilic poly(amino acid)-based one-pot coating and conjugation approach that can transform hydrophobic nanoparticle into water-solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…It is known that the presence of primary amines on the surface of PM induces cellular stress. 32,33 We found that PM is able to generate ROS inside cells (Supporting Information, Figure S7). However, polymer becomes cytotoxic if more amines are present in the design, and polymer becomes inefficient in inducing autophagy if no primary amines are present (Figure 3 and Supporting Information, Figure S2).…”
Section: ■ Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that the presence of primary amines on the surface of PM induces cellular stress. 32,33 We found that PM is able to generate ROS inside cells (Supporting Information, Figure S7). However, polymer becomes cytotoxic if more amines are present in the design, and polymer becomes inefficient in inducing autophagy if no primary amines are present (Figure 3 and Supporting Information, Figure S2).…”
Section: ■ Discussionmentioning
confidence: 94%
“…The chemical structure of the polymer used in this work is shown in Scheme , and its synthesis is based on our reported approach. , The polymer has a poly­aspartic acid backbone with three different chemical functional groups, such as oleyl, arginine, and primary amine. The hydro­phobic oleyl groups induce polymer micellization, guanidinium groups of arginine offer high cell uptake of polymer micelles, and primary amines offer autophagy up-regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported that PEG‐based coatings may introduce other problems such as nondegradation and hypersensitivity . Possible alternatives to PEG include synthetic polymers such as polyoxazolin, polyvinyl pyrrolidone, polyacrylamide, zwitterions, and their block copolymers, natural polysaccharides such as dextran, chitosan, hyaluronic acid, and heparin, biomolecules such as polyaminoacids, albumin, and biomembrane, as well as siliconate treatment . Biodegradable polymers including chitosan, poly(phosphoester) and polyglutamic acid have achieved great attention for medical applications since they could be enzymatically hydrolyzed and degraded into nontoxic small molecules and do not accumulate in the body .…”
Section: Safe‐by‐design Strategies For Nanomedicinementioning
confidence: 99%
“…Therefore, surface modification of MNPs can be regarded as one of the key elements for all applications being discussed. Here, the introduction of polymer surface coatings has been proven to impart enhanced suspension stability [14], protein repellence [15], solubility in a diverse set of environments [13,16], and adjustable surface charge [17]. For instance, both shielding and anti-fouling can be ascribed to poly(ethylene glycol)-based (PEG) surfaces as they are able to bind large amounts of water [18].…”
Section: Introductionmentioning
confidence: 99%